2022
DOI: 10.3390/ma15010356
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Thermoplastic Polyurethane Composites Filled with Powdered Buckwheat Husks

Abstract: Bio-based fillers for the polymer composites are still interesting from the scientific and industrial point of view, due to their low cost and renewable nature. In this work partially green composites were obtained by the mixing of thermoplastic poly(ester-urethane) with the unmodified and modified (by acetylation) grinded buckwheat husks. Obtained biocomposites were characterized in the terms of their chemical structure (FTIR), microstructure (SEM), thermal stability (TGA), thermomechanical properties (DMTA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…By-products from both the timber and agricultural industries have also become a source of fillers that can be used in the production of polymer-based composites [ 7 , 8 ]. Wood–Polymer composites (WPCs) combine the advantages of both synthetic polymers and lignocellulosic fillers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By-products from both the timber and agricultural industries have also become a source of fillers that can be used in the production of polymer-based composites [ 7 , 8 ]. Wood–Polymer composites (WPCs) combine the advantages of both synthetic polymers and lignocellulosic fillers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The studies carried out so far show that agricultural waste is a material with high application potential in the production of composite PUR foams. It has been shown that waste products such as buckwheat husks [ 7 ], walnut shells [ 12 , 20 ], plum stones [ 22 ], straw fibre [ 24 ], hemp fibre [ 25 ], wheat slops [ 26 ], rapeseed cake [ 21 ], soy and potato protein [ 27 , 28 ], sugar beet pulp [ 15 ], egg shell [ 29 ], ground coffee [ 30 ], keratin chicken feathers [ 31 ] and many others have a beneficial effect on the properties of foams. Another source of naturally derived fillers is the timber industry.…”
Section: Introductionmentioning
confidence: 99%
“…(26,27). A schematic diagram for the set-up used is shown in Figure (15). All the measurement was carried out at chem-Dep.…”
Section: Ablative Testsmentioning
confidence: 99%
“…Several different bio-based fillers were proposed, for example: hemp fiber, flax fibers, kenaf fiber], sugar palm fibers, roselle fibers, tea waste fibers, and cocoa pod husk fibers. Rice and buckwheat husks are examples of agriculture byproducts that can be applied as a filler in the preparation of polymer composites (14,15). On the other hand, the ablative properties of most polymers ablative composites (i.e., resistance to thermochemical corrosion and mechanical scouring as well as thermal stress caused by high-temperature and high-speed heat flux) are mainly determined by the structure of the polymer layer (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high hardness, good strength, high elasticity, wear resistance, tear resistance, and aging resistance [ 1 , 2 ], PUR is widely used [ 3 , 4 , 5 , 6 ]. However, it turns out that like other polymer materials [ 7 ], PUR also has its drawbacks.…”
Section: Introductionmentioning
confidence: 99%